2000
DOI: 10.1016/s0098-1354(00)00617-7
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term supply chain planning under demand uncertainty: customer demand satisfaction and inventory management

Abstract: This paper utilizes the framework of midterm, multisite supply chain planning under demand uncertainty (Gupta and Maranas, 2000) to safeguard against inventory depletion at the production sites and excessive shortage at the customer. A chance constraint programming approach in conjunction with a two-stage stochastic programming methodology is utilized for capturing the trade-off between customer demand satisfaction (CDS) and production costs. In the proposed model, the production decisions are made before dema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(62 citation statements)
references
References 7 publications
0
56
0
3
Order By: Relevance
“…This investigation may guide a service company's interest in suitable quality activities. Gupta et al (2000) suggested a model for settlement amongst customer demand satisfaction and manufacturing costs. In the recommended model, the production choices are made before demand acknowledgment and on the other side, the inventory network choices are postponed.…”
Section: Customer Expectationsmentioning
confidence: 99%
“…This investigation may guide a service company's interest in suitable quality activities. Gupta et al (2000) suggested a model for settlement amongst customer demand satisfaction and manufacturing costs. In the recommended model, the production choices are made before demand acknowledgment and on the other side, the inventory network choices are postponed.…”
Section: Customer Expectationsmentioning
confidence: 99%
“…In 2000, Gupta et al (2000) considered a mid-term, multi-site SC planning under demand uncertainty to safeguard against inventory depletion at the production sites and excessive shortage at the customer demand. In 2003, Gupta and Maranas (2003) developed a bilevel decision-making framework where production decisions are made "here-and-now" prior to the resolution of uncertainty, while the SC decisions are postponed in a "wait-and-see" mode.…”
Section: As Represented Inmentioning
confidence: 99%
“…The profit maximization problem was modeled as a dynamic program. Gupta et al (2000) utilized a framework of mid-term, multisite supply chain planning under demand uncertainty to safeguard against inventory depletion at the production sites and excessive shortage at the customer. Banerjee et al (2001) examined the effects of two controlled partial shipment approaches within a single supplier, multiple customers supply chain network through a series of simulation experiments under different operating conditions, based on the number of customers and the variability of their order sizes.…”
Section: Literature Reviewmentioning
confidence: 99%